2007
DOI: 10.2166/wst.2007.316
|View full text |Cite
|
Sign up to set email alerts
|

Aeration effect on the efficiency of swine manure treatment in a trickling filter packed with organic materials

Abstract: Effect of aeration rate on the removal of organic matter and nitrogen and on the formation of NH3, N2O and N2 was studied for an extensive biofiltration system packed with an organic media, which was used to treat pig manure. The results show high removal of BOD5 and TSS (99 and > or = 98%), independently of the four aeration rate tested (3.4-34 m3/m2 x h). Aeration rate > or = 4.4 m/h resulted in high ammonia stripping during start-up (> or = 1.0 kg NH3-N/m3 of swine manure treated), while using 3.4 m/h only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
1
4
0
4
Order By: Relevance
“…Buelna et al [29] obtained a nitrogen removal rate of 26% in the treatment of swine wastewater, with a total nitrogen load of 2300 mg L −1 , and a very low hydraulic load (0.017 m −3 m −2 day −1 ). Garzon Zuñiga et al [11] reported an efficiency of 50% in the removal of total nitrogen content in swine wastewater with 2080 mg L −1 of nitrogen and a very low hydraulic load (0.5 m −3 m −2 day −1 ). The main factors that limit the capacity of trickling filters for denitrification are excessive organic loads and the development of high populations of aquatic snails [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Buelna et al [29] obtained a nitrogen removal rate of 26% in the treatment of swine wastewater, with a total nitrogen load of 2300 mg L −1 , and a very low hydraulic load (0.017 m −3 m −2 day −1 ). Garzon Zuñiga et al [11] reported an efficiency of 50% in the removal of total nitrogen content in swine wastewater with 2080 mg L −1 of nitrogen and a very low hydraulic load (0.5 m −3 m −2 day −1 ). The main factors that limit the capacity of trickling filters for denitrification are excessive organic loads and the development of high populations of aquatic snails [6].…”
Section: Discussionmentioning
confidence: 99%
“…Buelna et al [29] reported an efficiency of phosphorus removal of 71% from an influent with a concentration of 180 mg L −1 and a very low hydraulic load (0.017 m −3 m −2 day −1 ). Garzon-Zùñiga et al [11] evaluated various aeration rates, and observed effluents with dissolved oxygen contents from 7 to 8.5 mg L −1 , from an influent with 0.05 mg L −1 . No reports were found regarding changes of electrical conductivity in treated swine wastewater with trickling filters.…”
Section: Discussionmentioning
confidence: 99%
“…By means of a mass balance, it was shown that 30% of the nitrogen was eliminated as N 2 and 10% as N 2 O. For swine manure, loading rates between 0.017 and 0.035 m 3 /m 2 /d are generally recommended to avoid clogging problems [29,31]. Due to the high concentrations of nutrients in manure, these values are up to 2000 times lower than the loading rates recommended for wastewater treatment.…”
Section: Manurementioning
confidence: 99%
“…Los efluentes de menor concentración fueron reportadas para la etapa de maternidad (Garzón-Zúñiga et al, 2009;Victorica et al, 2008); en efluentes de la etapa de maternidad Jay-Myoung et al 2004; reporta concentraciones semejantes. Concentraciones intermedias a los efluentes de destete, engorda y maternidad fueron reportadas por Garzón-Zúñiga et al (2007) y Aubry et al (2006). Cuadro 1.…”
Section: Características Y Variabilidad De Las Aguas Residuales Porcíunclassified